2018
DOI: 10.1007/s00018-018-2873-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of a novel miR-1825/TBCB/TUBA4A pathway in sporadic and familial ALS

Abstract: Genetic and functional studies suggest diverse pathways being affected in the neurodegenerative disease amyotrophic lateral sclerosis (ALS), while knowledge about converging disease mechanisms is rare. We detected a downregulation of microRNA-1825 in CNS and extra-CNS system organs of both sporadic (sALS) and familial ALS (fALS) patients. Combined transcriptomic and proteomic analysis revealed that reduced levels of microRNA-1825 caused a translational upregulation of tubulin-folding cofactor b (TBCB). Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
1
23
0
2
Order By: Relevance
“…Particularly, it was reported that 15 miRNAs were dysregulated including disease-relevant miR-34a and miR504, which are known to be, implicated synaptic vesicle regulation and cell survival (Rizzuti et al, 2018). Additionally, another important miRNA, namely microRNA-1825, was found to be downregulated in CNS of both sporadic and familial ALS patients (Helferich et al, 2018). Interestingly, reduced levels of microRNA-1825 was demonstrated to cause a translational upregulation of tubulin-folding cofactor b ( TBCB ) which consequently to depolymerization and degradation of tubulin alpha-4A ( TUBA4A ), which is encoded by a known ALS gene (Helferich et al, 2018).…”
Section: Dysregulation Of Microrna (Mirna) In Alsmentioning
confidence: 99%
“…Particularly, it was reported that 15 miRNAs were dysregulated including disease-relevant miR-34a and miR504, which are known to be, implicated synaptic vesicle regulation and cell survival (Rizzuti et al, 2018). Additionally, another important miRNA, namely microRNA-1825, was found to be downregulated in CNS of both sporadic and familial ALS patients (Helferich et al, 2018). Interestingly, reduced levels of microRNA-1825 was demonstrated to cause a translational upregulation of tubulin-folding cofactor b ( TBCB ) which consequently to depolymerization and degradation of tubulin alpha-4A ( TUBA4A ), which is encoded by a known ALS gene (Helferich et al, 2018).…”
Section: Dysregulation Of Microrna (Mirna) In Alsmentioning
confidence: 99%
“…Unlike other MT proteins linked to neurological disorders, TUBA4A expression increases dramatically (>50-fold) with age in humans, potentially explaining why a mutation in this gene may promote a late-onset disease (Tischfield et al, 2011;Smith et al, 2014;Clark et al, 2016). Interestingly, decreased levels of TUBA4A-mRNA have been found in the brain and spinal cord of sALS and fALS patients with mutations in SOD1 and C9orf72 (Helferich et al, 2018). Unfortunately, the impact of TUBA4A mutations in MT dynamics and how its expression changes over time have not been assessed in vivo.…”
Section: Tubulin Alpha 4a (Tuba4a)mentioning
confidence: 99%
“…Tubulin Alpha 4a ( TUBA4A) , encoding for α-tubulin, has been recently identified as a novel ALS gene (Smith et al, 2014). It has been shown that TUBA4A mutations are able to alter microtubule dynamics, with depolymerization and degradation of α-tubulin (Helferich et al, 2018). Although this gene has been described only in cohorts of ALS and FTD patients, a sensory and motor neuronopathy is observed in progressive motor neuronopathy mice mutated in tubulin binding cofactor E ( TBCE ), a known interactor of α-tubulin (Schafer et al, 2017).…”
Section: Pathogenic Mechanisms Of Pns Damage In Alsmentioning
confidence: 99%